IMPLEMENTASI MODEL COOPERATIVE LEARNING BERBANTUAN KOMPUTER DALAM PEMBELAJARAN PENDIDIKAN MATEMATIKA I PADA MAHASISWA PGSD - Trimurtini, - (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif]–> The aim of this study was to find out the outcome of the implementation of a computer-aided cooperative learning model in the learning and teaching of Mathematics Education I in PGSD FIP UNNES. The research problems were: (1) Does the skill proceed in applying the computer-aided cooperative learning model have an effect on the learning outcome of the PGSD students? (2) Is there any difference in the learning outcome of mathematics of PGSD students between the cooperative learning model and the conventional model? The study applied the experimental research design comparing the learning outcomes of students who were taught using the cooperative learning model and those who were taught using the conventional model. The results oh the study are: (1)There is a big influence (54,4%) of skill proceed in applying the computer-aided cooperative learning model to the learning outcome of PGSD students in Mathematics Education I; (2) The cooperative learning model is more effective than the conventional model in improving the learning outcome of PGSD students in Mathematics Education I.